Identifikasi Bahan Campuran Terhadap Warna Pada Winogradsky Column Menggunakan Air Sungai Dukun Jakung Desa Cilowong Kecamatan Taktakan Kota Serang - Nurhasanah, Nurhasanah; Novridasati, Liliana; Febby Handayani, Anggun; Nurfadilah, Silvi (Indobiosains, 2025)
The Winogradsky column was pioneered by Surgei Winogradsky, a Russian microbiologist. Winogradsky created an isolation tool, he showed how microorganisms play a role in maintaining ecosystem balance and deep sustainability. The aim of this research is to identify and study various microorganisms involved in the conversion of inorganic compounds in the natural environment. The research method uses a descriptive method, which observes and describes the behavior of microorganisms in various environmental conditions. The research was carried out in the Jakung Dusun River, Cilowong Village, Taktakan District, Serang City using glass bottles containing a mixture of water, soil and various other organic materials which allows the formation of gradients of nitrogen, oxygen and sulfur. The research results show that microorganisms can adapt to convert inorganic compounds into more complex compounds with redox reactions.